Victimization Within and Beyond the Prison Walls: A Latent Profile Analysis of Transgender and Gender Diverse Adults - Hughto, Jaclyn M. W. (Journal of interpersonal violence, 2022)
Background: Transgender and gender diverse (TGD) people are disproportionately incarcerated in the United States relative to the general population. A dearth of quantitative research has explored victimization as a risk factor for incarceration as well as the victimization experiences of formerly incarcerated TGD populations. Methods: In 2019, 574 TGD adults completed an online survey assessing sociodemographics, victimization across settings, and incarceration history. Latent class analysis was used to identify two sets of latent subgroups based on respondent's victimization experiences: 1) lifetime victimization (low; moderate; and high) and 2) classes of victimization while incarcerated (low; moderate; and high). Bivariate and multivariable logistic regression analyses examined sociodemographic, mental health, and lifetime victimization experiences associated with lifetime incarceration (Outcome 1). Among those with incarceration histories, bivariate hierarchical logistic regression analyses also explored the association between gender identity, race/ethnicity, HIV status, visual gender non-conformity, and class of victimization during incarceration (Outcome 2) . Results: Participants? mean age was 31.4 (SD = 11.2), 43.4% had a non-binary gender identity, 81.5% were White, non-Hispanic, 2.1% were living with HIV, and 13.2% had been incarcerated. In the multivariable model for Outcome 1, high levels of victimization, age, being a racial/ethnic minority, being a trans woman, living with HIV, and past-12-month polysubstance use were all associated with increased odds of lifetime incarceration (p-values < 0.05). In the bivariate hierarchical logistic regression analyses for Outcome 2, living with HIV and having a visually gender non-conforming expression were significantly associated with elevated odds of experiencing high levels of victimization while incarcerated (p-values < 0.05). Conclusion: Findings document the relationships between victimization and incarceration among TGD people as well as identify the subpopulations at greater risk for incarceration and experiencing victimization while incarcerated. Efforts are needed to prevent victimization across the life course, including while incarcerated and support TGD individuals in coping with the negative sequelae of victimization and incarceration experiences.